Induction of murine experimental autoimmune myocarditis – technical details, implementation and evaluation - Dudu, Felicia Luminita; Fueriu, Razvan Mihai; Jakobsson, Gabriel; Vlad, Mihaela Loredana; Lazar, Alexandra Gela; Manea, Simona Adriana; Manea, Adrian; Schiopu, Alexandru ; 0000-0002-7587-5050 (Romanian Journal of Cardiology / Revista Romana de Cardiologie, 2025)
Introduction: Myocarditis is a complex cardiac disorder with multifactorial etiology, characterized by myocardial inflammation, cardiomyocyte damage, and fibrosis. Left untreated, myocarditis may lead to acute and chronic heart failure and life-threatening arrhythmias. Reliable experimental models of myocarditis are required to study the underlying pathological mechanisms of the disease and to develop efficient therapies. Materials and Methods: Experimental autoimmune myocarditis (EAM) was induced by immunizing 9-week-old female BALB/c mice with a specific peptide derived from the cardiac α-myosin heavy chain (α-MHC) which is the major autoantigen recognized by heart-specific autoantibodies in myocarditis. The immunization activates an anti-α-MHC immune response, which triggers an inflammatory reaction leading to cardiomyocyte damage and myocardial injury. The mice received two immunizations with 100 μL of an emulsion containing α-MHC peptide emulsified 1:1 in Complete Freund’s Adjuvant (CFA) supplemented with 4 mg/mL inactivated Mycobacterium tuberculosis (M. tuberculosis), administered subcutaneously on Days 0 and 7. Results: We highlight the essential steps for the successful preparation of the peptide-adjuvant emulsion, a key factor in the effective implementation of the model, and mouse immunization. We also demonstrate how the inflammatory, fibrotic, and functional consequences on the myocardium should be evaluated. Conclusion: This efficient and reproducible murine EAM model allows experimental research on the pathophysiology and treatment of myocarditis.
Keywords: cardiac α-myosin heavy chain peptide; experimental autoimmune myocarditis; immune response; inflammation